Skull Base Trauma: Clinical Considerations in Evaluation and Diagnosis and Review of Management Techniques and Surgical Approaches - Feldman, Jacob S.; Farnoosh, Soroush; Kellman, Robert M.; Tatum, Sherard A., III (Seminars in Plastic Surgery, 2017)
Traumatic injuries to the skull base can involve critical neurovascular structures and present with symptoms and signs that must be recognized by physicians tasked with management of trauma patients. This article provides a review of skull base anatomy and outlines demographic features in skull base trauma. The manifestations of various skull base injuries, including CSF leaks, facial paralysis, anosmia, and cranial nerve injury, are discussed, as are appropriate diagnostic and radiographic testing in patients with such injuries. While conservative management is sometimes appropriate in skull base trauma, surgical access to the skull base for reconstruction of traumatic injuries may be required. A variety of specific surgical approaches to the anterior cranial fossa are discussed, including the classic anterior craniofacial approach as well as less invasive and newer endoscope-assisted approaches to the traumatized skull base.
Keywords: cranial base; skull base trauma; surgical approaches; anterior cranial fossa